Faktor untuk memprediksi purchase intention pada brand fashion Indonesia - Clarence Clarence; Keni Keni (Jurnal Manajemen Maranatha, 2022)
Consumer buying intentions can be predicted by digital marketing, customer engagement, and customer perceived value. This study aims to empirically test digital marketing, customer engagement, and customer perceived value, as well as brand preference in mediating customer perceived value on purchase intention. In this study, the sample collected was 217 respondents. Data were collected and distributed by online questionnaires using Google form and data analysis of this research uses PLS-SEM method. The result shown by this study shows digital marketing and customer engagement can predict purchase intention. Furthermore, customer perceived value cannot predict purchase intention directly, but customer perceived value can predict consumer purchase intention through brand preference. The results of this study are expected to be able to help companies to make the right marketing strategies by taking into account the factors that can predict consumer buying intentions.